Camisea 2.0: Evolution and outlook of the natural gasmarket in Peru - Torres Madrid, Francisco (2016)
The purpose of this paper is to analyze the exploration, production, transport pipelines and distribution phases of the Camisea Project. The author provides a brief overview of the various aspects of the project, through the identification of the main challenges and solutions applied in Peru. In addition, he describes the evolution of the project, its success, and its role in the development of a new époque for the natural gas industry in Peru, referred to as the second phase of Camisea and the inspiration for the title of this work. Most importantly, the goal of the paper is to provide the reader with an overview of one of the most important  infrastructure  projects of South America and it´s influence on the development of the Peruvian oil and gas market.